Development of a Cultural Tourism Village in Sambilegi Kidul based on Community Empowerment - Faridl Widhagdha, Miftah; Kevin Kurnia Gumilang (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The Cultural Tourism Village is a community empowerment strategy carried out by PT Pertamina Patra Niaga DPPU Adi Sucipto through the CSR Program in developing the community in Sambilegi Kidul Padukuhan, Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta Special Region Province. This program started with the findings of social problems, followed up through social mapping studies and limited group discussions with the community. Social issues in Sambilegi Kidul Padukuhan include the lack of optimal land use, the limited level of community welfare, and the fading of cultural preservation, especially Javanese culture in the community in Sambilegi Kidul Padukuhan. PT Pertamina Patra Niaga DPPU Adi Sucipto implements the Dangau Minahorti CSR Program which focuses on increasing public awareness of the environment, developing horticultural agriculture, developing aquaculture to preserving the traditional sport "Jemparingan". As a result, this program has succeeded in forming the Arimbi Women Farmers Group (KWT) consisting of 44 people who manage the business activities of Sambilegi Kidul Tourism Village. Now, Sambilegi Kidul Tourism Village has become an alternative tourist destination, especially cultural tourism in Sleman Regency and has become a leading tourism destination for the surrounding community.